2019
DOI: 10.21608/hjsc.2019.69701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spraying Fish Oil and Glutathione on Fruiting of Ewaise Mango Trees Grown under Sandy Soil

Abstract: This study was established during 2017 and 2018 seasons to test the effect of single and combined applications of fish oil and glutathione each at 0.5 to 2% on some vegetative growth aspects, photosynthetic pigments, flowering and fruit setting behavior, N, P, K, Mg, Ca (as %), Zn, Fe, Mn and Cu (as ppm), yield and both physical and chemical characteristics of the fruits in mango cv. Ewaise grown under sandy soil. The trees received three sprays at growth start, just after fruit setting and at 30 days later. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…These fertilizers are also a suitable mechanism for transporting compounds to the target places in the plant, whether leaves, roots or the rest of the plant parts [17] and [18]. These results agreed with [19], [20] and [21].…”
Section: Discussionsupporting
confidence: 63%
“…These fertilizers are also a suitable mechanism for transporting compounds to the target places in the plant, whether leaves, roots or the rest of the plant parts [17] and [18]. These results agreed with [19], [20] and [21].…”
Section: Discussionsupporting
confidence: 63%
“…[13] found in their study on effect of spraying glutathione on growth of grape vines with three concentrations (500 mg, 1 gm and 2 gm.L -1 ) and compared them to no spraying indicated that spraying led to a significant increase in leaves content of chlorophyll and NPK elements, and this increase increased with increasing spray concentrations. [14] Also found in his experiment on spraying three levels of glutathione (500 mg, 1g and 2g.L -1 ) alone or in combination with spraying fish oil on growth of mango trees that there was a significant increase in leaf area and leaf content of nitrogen and phosphorous, especially when spraying at the level of 2 g.L -1 . As for Kaolin clay, it is one of inert clay minerals, it consists mainly of aluminum silicate, and chemical formula is Al2Si2O5(OH)5.…”
Section: Introductionmentioning
confidence: 89%